SCHEMA AS COGNITIVE INSTRUMENT: READING NARRATIVE TEXT IN JUNIOR HIGH CLASSROOM :A Descriptive Qualitative Research of Seventh Grade Students at One of the Junior High Schools in Bandung - Mentari Putrirahayu Prawira, - (2017)
The research was aimed to describe one cognitive poetics instrument which is students' schemata and how it shapes students reading comprehension of the selected multicultural literary text titled How We Live by Anita Harper and Christine Roche (1977). The descriptive qualitative method was employed in this study. The data were obtained through observation, interview, and students' document as the instruments of the research. The data showed most of the schemata underlying students' reading comprehension were cultural schemata which help students in comprehending the multicultural text How We Live. Based on the result of the study, this study also gave light to the using of multicultural literature in teaching English for junior high students.---Penelitian ini bertujuan untuk menjabarkan salah satu instrument cognitive poetics yaitu schemata murid dan bagaimana murid memahami teks sastra multikultur tertentu yang berjudul How We Live karya Anita Harper dan Christine Roche (1977). Metode kualitatif deskriptif digunakan pada penelitian ini. Data didapatkan melalui observasi, wawancara, dan dokumen siswa sebagai instrument penelitian. Hasil data menunjukkan bahwa schemata yang mendasari siswa dalam pemahaman membaca didominasi oleh cultural schemata yang dimana schema tersebut membantu siswa dalam memahami teks How We Live. Berdasarkan hasil yang didapatkan dalam penelitian ini, penelitian ini memberi pencerahan pada penggunaan teks multikultur dalam pembelajaran bahasa inggris untuk siswa sekolah menengah.